2008
DOI: 10.1038/jp.2008.19
|View full text |Cite|
|
Sign up to set email alerts
|

Impact of early infant feeding practices on mortality in low birth weight infants from rural Ghana

Abstract: Improving early infant feeding practices is an effective, feasible, low-cost intervention that could reduce early infant mortality in LBW infants in developing countries. These findings are especially relevant for sub-Saharan Africa where many LBW infants are born at home, never taken to a health facility and mortality rates are unacceptably high.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
1
2

Year Published

2008
2008
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(28 citation statements)
references
References 21 publications
(18 reference statements)
0
25
1
2
Order By: Relevance
“…Because early breastfeeding is associated with exclusive and total breastfeeding duration, and the latter with reduced morbidity and mortality, it is reasonable to expect that early breastfeeding will reduce these poor outcomes. However, only two observational studies conducted in Ghana and Nepal evaluated the effect of early breastfeeding on neonatal mortality, both showing that delayed initiation was associated with higher neonatal mortality [293,294]. A third study from Egypt also reported increased diarrhea incidence in the first six months of life among babies who were put to the breast three or more days after birth [295].…”
Section: Resultsmentioning
confidence: 99%
“…Because early breastfeeding is associated with exclusive and total breastfeeding duration, and the latter with reduced morbidity and mortality, it is reasonable to expect that early breastfeeding will reduce these poor outcomes. However, only two observational studies conducted in Ghana and Nepal evaluated the effect of early breastfeeding on neonatal mortality, both showing that delayed initiation was associated with higher neonatal mortality [293,294]. A third study from Egypt also reported increased diarrhea incidence in the first six months of life among babies who were put to the breast three or more days after birth [295].…”
Section: Resultsmentioning
confidence: 99%
“…However, this finding should not be interpreted to mean that early initiation of breastfeeding is not important for child well‐being, as the neonatal and infant survival benefits of early initiation of breastfeeding are well established (Edmond et al . , , ; Mullany et al . ).…”
Section: Discussionmentioning
confidence: 99%
“…We know that exclusive breast feeding has a protective effect on overall mortality and morbidity from pneumonia and gastrointestinal infection, so it is important that we target these specific issues much more for mothers in these settings. [27][28][29][30][31][32] Despite health workers reporting their counselling of mothers on supporting their LBW baby (breast feeding, keeping the babies warm and recognition of illness), they also blamed mothers for lack of adherence to their advice. This is likely to be shaped in part by poor education and traditional beliefs, but our findings show challenges faced by caregivers are compounded by a general lack of support for mothers who have high expectations placed on them from health workers and communities.…”
Section: Lack Of Resourcesmentioning
confidence: 99%